Granting a nursing benefit to a person with an established right to an old-age pension (Discourse of Law and Administration, 2022)
The provision, according to which the nursing benefit is not due if the caregiver has an established right to an old-age pension, has become the basis for the development of three different lines of jurisprudence in practice. Two of them criticize the unequivocal result of a linguistic interpretation and, in their motives, seek to demonstrate the possibility of granting the right to a benefit to a person who has an established right to an old-age pension, the amount of which is lower than the amount of the benefit. At the same time, it is assumed that a different approach would violate the constitutional principle of equality. The legislator, using an unambiguous formulation of the negative condition for granting the right to a benefit, excludes from the group of beneficiaries all persons with the established right to a retirement pension - regardless of its amount. The introduction of exceptions in this respect by public administration bodies and administrative judiciary is an interference with the statutory matter. On the other hand, stating that Art. 17 sec. 5 point 1 lit. 1 of the Act on family benefits, excluding from the group of eligible persons with an established right to an old-age pension, the amount of which is lower than the nursing benefit, violates the constitutional principle of equality (Article 32 (1) of the Polish Constitution), interferes with the exclusive competence of the Constitutional Tribunal. Under the applicable law, it is not possible to grant the right to a nursing benefit to a person with an established right to an old-age pension – regardless of its amount.
Keywords: nursing benefit; retirement pension; social security; equality